2021
DOI: 10.3389/fimmu.2020.585399
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein SA-Positive Neutrophil Elicits Stronger Phagocytosis and Neutrophil Extracellular Trap Formation and Subdues Pro-Inflammatory Cytokine Secretion Against Streptococcus suis Serotype 2 Infection

Abstract: Streptococcus suis serotype 2 (SS2), an important zoonotic pathogen that causes septicemia, arthritis, and irreversible meningitis in pigs and humans, can be transmitted to humans from pigs. S. suis causes huge economic losses to the swine industry and poses a serious threat to public health. Previously, we found that the brain tissues of mice with SS2-induced meningitis showed disrupted structural integrity and significantly enhanced polymorphonuclear neutrophil (PMN) infiltration. We showed that the brain ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In the CNS, neutrophil infiltration would then be a consequence of the inflammation, and not a cause, such as in the systemic infection. Some studies confirmed that neutrophils contribute to the clearance of S. suis in the CNS since a higher neutrophil mobilization in the brain is associated with a decrease of bacterial load [76,133].…”
Section: Recruitment and Role Of Neutrophils In Central Nervous Syste...mentioning
confidence: 94%
See 2 more Smart Citations
“…In the CNS, neutrophil infiltration would then be a consequence of the inflammation, and not a cause, such as in the systemic infection. Some studies confirmed that neutrophils contribute to the clearance of S. suis in the CNS since a higher neutrophil mobilization in the brain is associated with a decrease of bacterial load [76,133].…”
Section: Recruitment and Role Of Neutrophils In Central Nervous Syste...mentioning
confidence: 94%
“…Among the 46 articles studying in vitro activation of neutrophils by S. suis, only 13 studies (28%) measured neutrophil purity after isolation [44,45,54,62,[69][70][71][72][73][74][75][76][77] (Figure 3). A diversity of methods were used to assess cell purity: Giemsa/Wright's stain [44,73,74], Hoechst stain (microscopy) [71,72] or flow cytometry using different markers (for exam-ple, Ly6G+, CD11b+) [54,[75][76][77]. However, in these studies, the purity was comprised between 75% and 97% and the high risk of contaminating cells probably compromised the interpretation of the results when the purity was low.…”
Section: Purity and Viability Of Neutrophils 231 Isolation Methods An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation plays a crucial role in the pathogenesis of systemic and CNS infections caused by SS2 (Gottschalk et al, 2010). The pathogen induces excessive production of proinflammatory cytokines and recruitment and activation of different leukocyte populations, leading to inflammation in the central system (Sun et al, 2020). Central nervous system inflammation can lead to intracranial complications, including cerebral edema, increased intracranial pressure, and cerebrovascular damage (Fittipaldi et al, 2012).…”
Section: Pathogenic Process Of Ssmentioning
confidence: 99%
“…Vania et al [17] showed that RPSA is involved in maintaining cell viability through apoptotic evasion, allowing tumor progression. RPSA is a complex protein with diverse functions and plays a major role in an in ammatory response, mediating cell adhesion, migration, proliferation, and survival [18][19][20].…”
Section: Introductionmentioning
confidence: 99%